A comparison of the performance of the I-gel™ vs. the LMA-S™during anesthesia: a meta-analysis of randomized controlled trials. - Xiaoguang Chen (Public Library of Science (PLoS), 2013)
Background and objective Conflicting results were found between the I-gel™ and the LMA-Supreme™ during anesthesia, so we conducted a meta-analysis of randomized controlled trials (RCTs) to compare the effectiveness and safety of the I-gel™ vs. the LMA-Supreme™during anesthesia. Methods A comprehensive search was conducted using Pubmed, EMbase, ISI Web of Knowledge, the Cochrane Library, China Journal Full-text Database, Chinese Biomedical Database, Chinese Scientific Journals Full-text Database, CMA Digital Periodicals, and Google scholar to find RCTs that compare the LMA-S™ with the i-gel™during anesthesia. Two reviewers independently selected trials, extracted data, and assessed the methodological qualities and evidence levels. Data were analyzed by RevMan 5.0 and comprehensive meta-analysis software. Results Ten RCTs were included. There were no significant differences in oropharyngeal leak pressures (mean difference [MD] 0.72, 95% confidence interval [CI] -1.10 2.53), device placement time (MD -1.3, 95%CI -4.07 1.44), first attempt insertion success (risk ratio [RR] 1.01, 95% CI 0.9 1.14), grade 3 and 4 fiberoptic view (RR 0.89, 95%CI 0.65 1.21), and blood on removal (RR 0.62, 95%CI 0.32 1.22) between the i-gel™ and the LMA-Supreme™, respectively. However, the LMA-Supreme™was associated with easier gastric tube insertion (RR 1.17, 95%CI 1.07 1.29), and more sore throat (RR 2.56, 95%CI 1.60 4.12) than the i-gel™ group. Conclusions The LMA-Supreme™ and i-gel™ were similarly successful and rapidly inserted. However, the LMA-Supreme™ was shown to be easier for gastric tube insertion and associated with more sore throat compared with the i-gel™.